Research self-efficacy as a predictor of research quality of life among graduate students - Mallouh Al-Fadhli, Hoda (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
The study aimed to reveal the nature of the relationship between research self-efficacy and quality of life and to verify the possibility of the contribution of research self-efficacy in predicting the quality of research life in a sample of (120) graduate students from the faculties of Social Sciences and Humanities at Kuwait University, Applied to her two measures of research self-efficacy, and quality of life research preparation/ researcher. The results indicated that the individuals of the study sample have average levels in both research self-efficacy and Research life quality, and the results also indicated that there is a positive relationship between research self-efficacy and Research life quality; in addition to the predictability of the quality of their research life through their research self-efficacy.